Implementasi Sistem Informasi DANA untuk Efisiensi Transaksi Digital - Laurentius Chandika Laiglety; Raky Rajulio; Yustian Servanda; Nasruddin bin Idris (Nolsatu Publisher, 2026)
The rapid growth of digital transactions in Indonesia has increased the demand for efficient, secure, and stable information systems. DANA, as one of the largest digital wallets, plays a crucial role in providing fast payment services. This study aims to analyze the implementation of information systems in the DANA application, focusing on system architecture and data processing that support transaction efficiency. A descriptive-qualitative case study method was employed through literature review, technical documentation analysis, and application feature observation. Results show that DANA's microservices architecture, real-time data processing, and distributed cloud infrastructure significantly accelerate transactions (average 5 seconds) and achieve 99% uptime. In conclusion, structured and adaptive information system implementation greatly contributes to the speed, security, and operational efficiency of DANA as a digital transaction platform.